Epidemiological profile of gestational syphilis cases in the municipalities of Paraná on the border between Brazil and Paraguay (Research, Society and Development, 2022)
Objective: To analyze the epidemiological profile of patients affected by Syphilis in the border cities between Brazil and Paraguay in the State of Paraná. Methodology: This is a cross-sectional survey, with a quantitative approach, using public domain data, through the TABNET application from the Informatics Department of the Unified Health System (DATASUS). For data collection, records were considered from 2011 to 2021 and the information was collected between September and October 2022. Simple descriptive statistics were used for data analysis. Results: The present study shows a growing trend in the number of cases of the disease over the years, pointing out that the largest number is in pregnant women aged 20 to 39 years with incomplete or complete high school education, these being pregnant women of color white. With regard to the clinical profile, the largest number of pregnant women were diagnosed in the Primary Phase of the disease, it was shown that the number of records classificated as ignored was elevated. However, most of the pregnant women who had complete data adhered to the treatment. Conclusion: The epidemiological characterization of Syphilis in border municipalities may contribute to the planning of intervention and educational actions, such as the rapid test and active search by the health teams of the Family Strategy Units in order to reduce the contaminated population index.